SISTEM PENYIRAM TANAMAN CABAI OTOMATIS UNTUK MENJAGA KELEMBABAN TANAH BERBASIS ESP8266 - Priyono, Andi; Triadyaksa, Pandji (BERKALA FISIKA, 2020)
The process of planting certain plants requires extra attention, especially in maintaining soil moisture such as in chili plants. Therefore, this research develops an automatic plant watering system that can be monitored via a smartphone using the Telegram application. This system can do automatic watering according to soil moisture and measures the temperature and humidity of the surrounding environment controlled by ESP8266 which is equipped with 16x2 LCD, YL-69 sensor, and DHT11 sensor. Watering system trials show excellent readability comparable to calibrators. Temperature, humidity, and soil moisture are informed via a smartphone and LCD that are attached to the watering prototype. The Telegram application is able to send information to carry out the function of watering automation when the soil moisture is less than 50% as a reference in accordance with the characteristics of the chili plants. In addition, the automatic sprinkler trial via the Telegram command, as desired by the user, was also successfully carried out. It is concluded that development of a plant watering system based on soil moisture information has been successfully carried out. The system shows the ability of the Telegram application to provide remote commands to the system that works.Keywords: Automatic plant watering system, ESP8266, Sensor YL-69, Sensor DHT11, Chili plants, Telegram